1992
DOI: 10.1182/blood.v80.8.1998.bloodjournal8081998
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of the hemostatic system during childhood

Abstract: The hemostatic system is assumed to be similar in children and adults and reference ranges established for adults are commonly used to evaluate children suspected of having congenital or acquired hemostatic problems. However, we know that the hemostatic system is not fully mature by 6 months of age and comprehensive studies of healthy older children have not been published. Therefore, we conducted a prospective cohort study of the hemostatic system in healthy children having minor, elective day surgery. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
142
0
10

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(157 citation statements)
references
References 0 publications
5
142
0
10
Order By: Relevance
“…After 2-4 h treatment, target anti-Xa ranges reported for children were 0.5-1.0 U ml À1 for dalteparin, nadroparin and tinzaparin (Nohe et al, 1999;Hofmann et al, 2001;Kuhle et al, 2005), and 0.4-1.0 U ml À1 for enoxaparin and reviparin-sodium (Massicotte et al, 1996(Massicotte et al, , 2003b; target ranges administered for prophylaxis in children following the initial treatment phase were 0.1-0.3 U ml À1 for enoxaparin, dalteparin and reviparin-sodium, and 0.2-0.4 U ml À1 for nadroparin, respectively (Massicotte et al, 1996(Massicotte et al, , 2003aHofmann et al, 2001). The LMWHs enoxaparin, dalteparin, nadroparin, reviparin and tinzaparin have all been used off-label in children (Andrew et al, 1992;Streif et al, 2003;Massicotte et al, 1996;Nohe et al, 1999;Dix et al, 2000;Punzalan et al, 2000;DeVeber et al, 2001;Hofmann et al, 2001;Nowak-Göttl et al, 2001a, b;Shama et al, 2002;Ho et al, 2004;Kosch et al, 2004;Michaels et al, 2004;Revel-Vilk et al, 2004;Kreuz et al, 2006;Merkel et al, 2006;Schobess et al, 2006). The aforementioned LMWHs have been used effectively for the treatment of venous thrombosis, including pulmonary embolism, thrombosis of the upper and lower venous system, catheter-induced thromboses, renal vein thrombosis, and cerebral venous thrombosis.…”
Section: Use Of Lmwh In Children With Thrombosismentioning
confidence: 99%
“…After 2-4 h treatment, target anti-Xa ranges reported for children were 0.5-1.0 U ml À1 for dalteparin, nadroparin and tinzaparin (Nohe et al, 1999;Hofmann et al, 2001;Kuhle et al, 2005), and 0.4-1.0 U ml À1 for enoxaparin and reviparin-sodium (Massicotte et al, 1996(Massicotte et al, , 2003b; target ranges administered for prophylaxis in children following the initial treatment phase were 0.1-0.3 U ml À1 for enoxaparin, dalteparin and reviparin-sodium, and 0.2-0.4 U ml À1 for nadroparin, respectively (Massicotte et al, 1996(Massicotte et al, , 2003aHofmann et al, 2001). The LMWHs enoxaparin, dalteparin, nadroparin, reviparin and tinzaparin have all been used off-label in children (Andrew et al, 1992;Streif et al, 2003;Massicotte et al, 1996;Nohe et al, 1999;Dix et al, 2000;Punzalan et al, 2000;DeVeber et al, 2001;Hofmann et al, 2001;Nowak-Göttl et al, 2001a, b;Shama et al, 2002;Ho et al, 2004;Kosch et al, 2004;Michaels et al, 2004;Revel-Vilk et al, 2004;Kreuz et al, 2006;Merkel et al, 2006;Schobess et al, 2006). The aforementioned LMWHs have been used effectively for the treatment of venous thrombosis, including pulmonary embolism, thrombosis of the upper and lower venous system, catheter-induced thromboses, renal vein thrombosis, and cerebral venous thrombosis.…”
Section: Use Of Lmwh In Children With Thrombosismentioning
confidence: 99%
“…Adopting therapies and treatment guidelines developed for adult populations for use in infants is problematic 3 . Nearly every component of the hemostatic system undergoes qualitative and quantitative changes from neonatal life to adulthood 7‐12 . Recent studies have shown that even the structure of fibrin clots differs substantially between infants and adults, and both differ in structure from clots produced from infant blood mixed with adult blood 13 .…”
Section: Introductionmentioning
confidence: 99%
“…These include factors such as hemostatic system immaturity, hemodilution, systemic inflammation, prolonged bypass times, and the use of deep hypothermic circulatory arrest (DHCA). [4][5][6][7] Increased bleeding and allogeneic blood transfusion requirements have been shown to vary inversely with the age and size of infants requiring cardiac surgery. 8 Transfusion of allogeneic blood products is associated with a number of adverse effects such as infectious agent transmission, the development of postoperative infections, and other transfusion reactions.…”
mentioning
confidence: 99%